Challenges for sustainable water use in the northern part of Pakistan focusing on hydrology assessment of non-industrial zone. (15th May 2022) - Hayder, Rizwan; Hafeez, Muhammad; Zaheer, Muhammad
Abstract: The current study was focused on the water quality assessment of the District Muzaffarabad (DMZD) Azad Jammu and Kashmir (AJK), the northern part of Pakistan. The qualitative assessment was done on the surface water bodies, spring waters and tap water sources of DMZD. A total of eight parameters were assessed in this exploration including physical parameters, microbiological analysis, anion detection, and heavy metal exploration. Some physical parameters i.e., Electrical Conductance and Total Dissolved Solid showed higher variance than WHO allowed limits having a positive correlation within themselves that has indirectly affected the water quality of the region. Microbiological analysis was also performed using 3M-petrifilms with a capacity to quantify and distinguish between coliforms and E. coli by producing different stains on the surface chromophore of the petrifilm. Amongst eighty collected samples, more than 90% were contaminated with bacteria i.e., coliforms or E. coli . Poor water management and open disposal of sewage, sludge and other waste products were the main causatives of bacterial pollution. The significant anions which were crossing the maximum concentration limits (MCL) were fluoride, nitrite and nitrate (2.981 mg/L, 0.418 mg/L and >30 mg/L). Amongst anions especially, nitrite and nitrate were the real culprits of many health-related issues in humans' i.e., cancers, etc. and fluorides were responsible for diseases such as dental fluorosis, skeletal fluorosis etc. Water quality was generally poor and unsafe in the studied areas. We have also analyzed heavy metal content in the water samples collected from DMZD, AJK. Heavy metals ions detected in the collected water samples were; Arsenic (As 3+ ), Copper (Cu 2+ ), Iron (Fe 2+ ), Lead (Pb 2+ ) and Nickel (Ni 2+ ) . We used robust Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) for heavy metal detection having broader LoD for a variety of turbid samples especially. Along with some fluctuations in the concentrations of other heavy metals, a significant spike was observed for Pb 2+ (0.01818 mg/L) in ICP-OES experiments exceeding from MCL (0.01 mg/L) of lead setup by WHO. A higher concentration of Pb 2+ was due to anthropogenic sources and natural sources in District Muzaffarabad. The study was aimed to find out the cause of the recent upsurge of different lethal diseases (gastrointestinal, cardiovascular, cancers etc.) in the region relative to water contamination. From this study and application of analytical methods we have revealed meaningful information about the unexplored water quality data of the studied area. Graphical abstract: Image 1 Highlights: A Total of eighty water samples have been analyzed for their quality parameters. Among physicochemical parameters significant fluctuations were observed. More than 90% of samples were contaminated with microbial contaminants. Heavy analysis showed high Pb concentration in the studied area.